2018
DOI: 10.1088/1361-6560/aaceb8
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid simulation framework for computer simulation and modelling studies of grating-based x-ray phase-contrast images

Abstract: Clinical studies performed using computer simulation are inexpensive, flexible methods that can be used to study aspects of a proposed imaging technique prior to a full clinical study. Typically, lesions are simulated into (experimental) data to assess the clinical potential of new methods or algorithms. In grating-based phase-contrast imaging (GB-PCI), full wave simulations are, however, computationally expensive due to the high periodicity of the gratings and therefore not practically applicable when large d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The interferometer operated at 40 kVp with a 2 μm G2 grating period and a system visibility of 22%. The radiation dose per round was 0.51 mGy [19,20]. From the acquisitions, dark field images were reconstructed through a MATLAB-algorithm.…”
Section: Dark Field Imagingmentioning
confidence: 99%
“…The interferometer operated at 40 kVp with a 2 μm G2 grating period and a system visibility of 22%. The radiation dose per round was 0.51 mGy [19,20]. From the acquisitions, dark field images were reconstructed through a MATLAB-algorithm.…”
Section: Dark Field Imagingmentioning
confidence: 99%
“…Pups were anaesthetized for the imaging with Isoflurane (2.5 MAC, 2,5%, 2l/min, ISO-VET®, EuroVet, Heusden-Zolder, Belgium) delivered via a nose cone. Dark field imaging was performed using a Talbot-Lau interferometer operating at 40 kVp with a 2 μm G2 grating period and system visibility of 22% (44). The radiation dose per round was 0.51 mGy expressed in entrance air Kerma.…”
Section: Methodsmentioning
confidence: 99%
“…The radiation dose per round was 0.51 mGy expressed in entrance air Kerma. DF and conventional attenuation images were reconstructed from the X-ray acquisitions (31,44). DF signal strength was scored in 4 lung quadrants relative to control images.…”
Section: Methodsmentioning
confidence: 99%
“…There is a limited number of computational studies in the field of phase-contrast grating imaging reported in the literature [19][20][21][22][23][24]. All these studies are based on the use of simple objects, such as spheres and cylinders, and aim at proof of concept and optimisation of dose and imaging parameters.…”
Section: Introductionmentioning
confidence: 99%